Good Corporate Governance, Leverage, and Risk Management in Financial Performance Analysis: Tata Kelola Perusahaan yang Baik, Leverage, dan Manajemen Risiko dalam Analisis Kinerja Keuangan - Audhy Hermaphilia; Ela Widasari; Siti Mudawanah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Corporate financial performance is intricately linked with governance structures and financial strategies. Specific Background: In Indonesia’s mining sector, understanding how Good Corporate Governance (GCG) and Leverage influence performance through risk management remains underexplored. Knowledge Gap: Prior studies lack clarity on whether GCG and Leverage directly or indirectly impact financial outcomes via risk mitigation. Aim: This study investigates the effects of GCG components (institutional ownership, independent board of commissioners, audit committee) and Leverage (debt-to-equity ratio) on Return on Assets (ROA), incorporating risk management as an intermediary variable. Results: Utilizing SPSS 25 for descriptive analysis, classical assumption tests, and path analysis across 27 IDX-listed mining companies from 2019–2023, the results show that no independent variable significantly affects ROA collectively. However, the independent board of commissioners significantly influences risk management, which itself has no subsequent impact on financial performance. Novelty: This study highlights the limited mediating role of risk management, challenging assumptions about its integrative influence on financial outcomes. Implications: The findings enrich corporate finance theory and suggest organizations must realign risk governance frameworks to enhance budget execution and capitalize on strategic opportunities. Highlights: Reveals limited impact of GCG and Leverage on ROA. Highlights the significant role of independent commissioners in risk management. Challenges the assumption that risk management boosts financial performance. Keywords : Good Corporate Governance, Leverage, Financial Performance, Risk Management, Path Analysis